A numerical approach to slip flow of a micropolar fluid above a flat permeable contracting surface - Parthiban, R.; Palani, Govindasamy; Tinker, Seema; Sharma, Ram Prakash (Zielona Góra: Uniwersytet Zielonogórski)
A plain linear penetrable contracting sheet with slip over a micro-polar liquid with a stagnation-point flow is analyzed. Through similarity mapping, the mathematical modeling statements are transformed as ODE`s and numerical results are found by shooting techniques.
Keywords: boundary layers; heat sink; micro-polar fluid; slip condition; and suction or injection